2018
DOI: 10.26442/terarkh2018908131-136
|View full text |Cite
|
Sign up to set email alerts
|

On respiratory manifestations of gastroesophageal reflux disease

Abstract: One of the manifestations of gastroesophageal reflux disease (GERD) is extraesophageal symptoms, in particular, from the upper and lower respiratory tract. Gastroesophageal reflux is capable of both causing respiratory symptoms independently and aggravating the course of already existing diseases of the respiratory system. The article presents available in the literature current information on the pathogenesis of GERD respiratory symptoms, their clinical course, considerations of diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…Патология желудочно-кишечного тракта при БА встречается весьма часто. Особый интерес представляет патологический гастроэзофагеальный рефлюкс (ГЭР), рассматриваемый в качестве триггера приступов астмы, преимущественно в ночной период [3,4,5].…”
Section: актуальностьunclassified
“…Патология желудочно-кишечного тракта при БА встречается весьма часто. Особый интерес представляет патологический гастроэзофагеальный рефлюкс (ГЭР), рассматриваемый в качестве триггера приступов астмы, преимущественно в ночной период [3,4,5].…”
Section: актуальностьunclassified
“…Разом з тим, тільки у 30 % хворих, у яких виявлено обидва діагнози, ГЕРХ є причиною виникнення астми. В цілому, респіраторні прояви (кашель, задишка, утруднене дихання, напади задухи) стоять на першому місці серед позастравохідних проявів ГЕРХ і складають понад 30 % серед хворих на ГЕРХ [2,5,1].…”
Section: особенности течения хронического бронхита у больных с сопутсunclassified
“…Studies have shown that respiratory symptoms and pulmonary function changed in patients with intestinal bowel disease (IBD) and intestinal bowel syndrome (IBS) even without acute or chronic respiratory diseases [ 10 , 11 ]. Gastroesophageal reflux disease would cause respiratory symptoms and aggravate the existing respiratory diseases [ 12 ]. Researchers have also found that lipopolysaccharide (LPS) atomization and high-calorie diet synergistically promoted the pulmonary inflammatory process in rat, that is relevant to the change in gut microbiota [ 13 ].…”
Section: Introductionmentioning
confidence: 99%